Role of life events in the onset of obsessive compulsive disorder - Chetali Vijay Dhuri (Sri Lanka Journal of Psychiatry, 2014)
Introduction: Research into the onset of obsessive-compulsive disorder (OCD) suggests the occurrence of potential life events as triggering factors; however, such an association has not been well established. Aim: To assess the role of life events in the onset of OCD. Methodology: Fifty patients, ages ranging from 18 to 60 years, belonging to either sex, meeting the DSM-IV TR diagnostic criteria for OCD and attending a tertiary care psychiatric clinic were selected for the study. The Presumptive Stressful Life Events Scale (PSLES) was administered to them to obtain information regarding the presence of life events in a one year period prior to the onset of OCD. Other specific life events not included in the PSLES were also noted. Results: Sixty four per cent of the sample was male and 78% of the sample experienced stressful life events in the year prior to the onset of symptoms. Appearing for an exam or interview was most frequent (10%), followed by violation of religious or cultural beliefs (8%) and the death of a close family member (6%). A third of the females studied had life events relating to the reproductive cycle. Half of the sample had onset of OCD during adolescence with 75% of them subjects reporting preceding stressful life events. Conclusion: Life events appear to have a close association with the onset of OCD.  These findings suggest that life events may act as triggers predisposing vulnerable individuals to develop the disorder. DOI: http://dx.doi.org/10.4038/sljpsyc.v5i1.6341 SL J Psychiatry 2014; 5 (1): 10-13